(untitled) (Archives of Criminology, 2023)
One of the main concerns of the 1975 Austrian criminal law reform was to largely avoid the execution of short prison sentences. Due to their predominant disadvantages, they were to be replaced with fines wherever possible, and the execution of short custodial sentences was to be suspended as a subsidiary measure. Under Section 37 of the Austrian Criminal Code, a short custodial sentence for an offence that carries a maximum term of imprisonment of ten years is to be replaced by a monetary penalty if the court deems it justifiable for preventive reasons.